General Description of Serotonin Theory - Yusra A. Radeef; Zahraa Ali Abdullah (Zien Journals, 2023)
This research review sheds light on an overview of serotonin and its relationship with cases of depression. The chemical activity of serotonin has been addressed, as serotonin acts as chemical messengers that act on cells throughout the human body, which starts from the calculus of early development and during puberty. In this research, we discuss how to increase serotonin through the use of drugs, which is an important field in psychiatric and biological research. We determine the normal range of serotonin in the blood through a simple blood test. The functions of serotonin, which is considered as a direct-acting neurotransmitter that is commonly stored in presynaptic vesicles. And we define the side effects and the expected results of reducing the natural ratio of serotonin in the human body
Keywords: Serotonin; 5-hydroxytryptamine; nervous system